Fluid flow simulation over complex shape objects using image processing to achieve mesh generation. (2017) - Lassoued, Khaoula; Sophy, Tonino; Jouanguy, Julien; Le-Moyne, Luis
In the domain of flow simulation, avoiding the manual conception and numerisation of the domain can lead to the saving of a certain amount of time. Some processes, using heavy devices like LASER metrology, allow the numerical reconstruction of a real object. The aim of this paper is to propose a more simple tool requiring a commercial digital camera (like a smartphone), to transform a digital picture into a ready to use mesh. Besides simplicity, the tool has to be precise enough to bring accurate simulation results. Then, image processing object detection and reconstruction are used to generate a 2D mesh that can be integrated in a finite volume transient CFD simulation. Cars and airfoils are chosen as objects and the DNS fluid flow Gerris solver performs the simulations. After a validation on a circular shape object, simulations, conducted at different Reynolds number, provide accurate results plotting the Von Karman alley regime.